Post-Marriage Division of Matrimonial Property (Harta Sepencarian) in Malaysian Shariah Court - Noorul Huda, Sahari; Siti Khadijah, A. M (Global Journal Al-Thaqafah, 2024)
Halal in Islam is a wide concept. It does not only cover dietary consumption, indulgence and services but also other matters under the rubric of halal and haram including the division of matrimonial property. The practice of dividing matrimonial property is often associated with unfairness to the claiming parties due to the non-clarity of the existing provision in providing appropriate and fair methods. The current provision causes the court to adopt different interpretations in ascertaining allocated shares to the divorced parties. This is mainly because contribution is considered as a sole criterion in dividing the assets. Other factor such as well-being of the minor dependent are often disregarded. Thus, the study aims to examine the effective law being used by the court in dividing matrimonial property of those couple who have divorced. Content analysis was conducted on a carefully selected sample of unreported cases, collected from six zones representing Shariah Courts in Malaysia. A total of 215 samples were selected for the study where analysis was made based on several variables such as the mode of division, scope of matrimonial asset, elements of consideration and proportion of share. Finding of this study indicates that contribution remains as a sole criterion used by the court to determine the share of parties. Thus, this study suggests that in order to commensurate the actual practice of the Shariah Court, it is pertinent that the issue should be resolved by amending the existing law, taking into consideration a lot of other factors for fair and equitable proportions in the division of matrimonial assets thereby preserving the halal status of the property dispersal.